An Emerging Digital Wall - Chu, C. Y. Cyrus. author. aut Link
XXI, 318 p. 9 illus., 6 illus. in color.
Keywords: This monograph focuses on conflicts in ICTs (information and communications technologies) in the context of the US-China standoff. The author identifes important aspects of ICT development and also discusses, with respect to each aspect the strategies adopted by both the U.S. and China. The topics discussed include high-tech industries’ decoupling, export controls and the entity list, regulations of foreign platforms, cyberspace trade barriers, blockchain and its applications, big data and AI, cyberattacks and penetrations, and international backlashes in the digital era. These ICT strategic interactions together gradually forge a digital wall, which is expected to divide the world into two digital camps (roughly, democratic and authoritarian). Between these two camps, the ICT industries are decoupled, the corresponding supply chains are partly separated, the data collection across camps is restricted, the infrastructure networking is segregated, and various ICT applications are more or less autarkic. The author was previously the minister for Science and Technology in Taiwan. C. Y. Cyrus Chu received his Ph.D. (Economics) from the University of Michigan (1985), and was a John Olin Fellow at Stanford Law School (1991-92), and a Rockefeller Foundation Fellow at U.C. Berkeley (1992-93). He is an elected Academician (2008), and currently a distinguished research fellow, of Academia Sinica, Taiwan. He is also an elected Foreign Member of the U.S. National Academy of Sciences (2017). He has been serving as an Editorial Board Member of the prestigious Journal PNAS (Proceedings of the National Academy of Sciences of the United States) since 2022. .